Kontestasi Hukum Internasional dalam Kebijakan Hilirisasi Indonesia - Mery, Lisa (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
This research aims to analyze Indonesia's ability as a country to utilize various international legal instruments in initiating political, economic and social goals, the study identifies the substantive instruments used, the challenges faced and the implications of Indonesia's foreign policy. Normative research method by analyzing international law rules and case studies through international agreements that have been ratified by Indonesia. The research results show that International Law has a significant influence on the formation of national legislation, there are a number of challenges and opportunities because the application of International Law requires effective and rational implementation.